PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MODERASI - Amin Wahyudi, Hasni Dyah Kurniawati (Universitas Slamet Riyadi, 2015)
The high employee performance is a feat achieved by the employee at a certain level. The purpose of this research is to determine the significance of the effect of job satisfaction and organizational commitment to performance with Organizational Citizenship Behavior (OCB) as a moderating variable in hospital employees in Karanganyar. The collection of data in the form of a questionnaire reply as the primary data and the literature as secondary. The number of samples are 107 employees with cluster sampling method with random sampling. Data analysis methods used are validity and reliability, the classical assumption, hypothesis testing Moderated Regression Analysis. Moderated Regression Analysis Results of calculation I shows the performance of hospital employees in Karanganyar affected by job satisfaction, Organizational Citizenship Behavior and interaction of the two. In individual job satisfaction affect the performance of hospital employees in Karanganyar. Organizational Citizenship Behavior significantly moderate the effect of job satisfaction on employee performance hospital. In individual organizational commitment affect the performance of hospital employees in Karanganyar. Organizational Citizenship Behavior variables showed significantly moderate the influence of organizational commitment to employee performance. Keywords: Job Satisfaction, Organizational Commitment, Organizational Citizenship Behavior, Performance.